Effectiveness of injury prevention programs in youth soccer players: a systematic review - Boza-Mendoza, José Geovanny (Sport Science Training and Research, 2026)
Introduction: Youth soccer is a significant cause of injury due to the high physical demands and the growth and development processes involved, making this population susceptible. In this regard, injury prevention programs have emerged as a measure to reduce the risk of injury and safeguard the health of the young athlete. Objective: To analyze the effectiveness of injury prevention programs in young soccer players on the incidence and severity of injuries. Methodology: A systematic review was conducted following the PRISMA 2020 statement. The search was conducted in the Scopus and Web of Science databases, yielding 514 initial records. After applying strict inclusion and exclusion criteria, 15 studies were eligible for qualitative analysis. Results: The results show that neuromuscular and strength training programs are effective in reducing the incidence and severity of injuries. Specifically, reductions of up to 56% in certain injuries, such as anterior cruciate ligament and shoulder injuries, are reported. Discussion: The effectiveness of injury prevention programs depends not only on their content but also on proper implementation and adherence, with contextual and organizational factors playing an important role in the outcomes. Conclusions: The evidence supports injury prevention as a safety measure for youth soccer players. Its systematic and mandatory inclusion in training sessions is essential for improving long-term health and athletic performance.